Transvaginal Resection of an Ovarian Fibroma Presenting as Meigs Syndrome - Wei-Hsi Chang; Chi-Huang Chen; Jah-Yao Liu (Elsevier, 2005)
Objective: Ovarian fibromas are benign neoplasms that arise from the stromal connective tissue of the ovary and constitute 4% of all ovarian neoplasms. We report a case of a twisted ovarian fibroma with ascites and mild pleural effusion which was removed through the vagina under laparoscopic assistance. Case Report: A 45-year-old female who had suffered from intermittent low back and pelvic pain for a year experienced an exacerbation in pain in the few months before admission. Sonography revealed ascites and a pelvic mass 15 cm in diameter and solid in appearance. After laparoscopic inspection and frozen section study to rule out ovarian malignancy, the tumor was removed vaginally. Conclusions: Ovarian fibroma with Meigs syndrome can be differentiated from ovarian malignancy with the assistance of pelvic sonography, laparoscopy and intraoperative frozen section study of the tumor. Once ovarian malignancy is ruled out, ovarian fibroma can be excised vaginally.